Psyche Mission System Level Guidance, Navigation, and Control Off-Nominal Testing - Arthur, Paige; Navarro, Jessica; Sover, Kimberly; Sternberg, David; Twu, Philip (2024 IEEE Aerospace Conference, 2024)
"Psyche: Journey to a Metal World" is a discoveryclass NASA mission to explore the largest known metal asteroid, (16) Psyche, to determine if it is the exposed core of a planetesimal. Led by principal investigator Dr. Lindy Elkins-Tanton of Arizona State University, Psyche is a collaboration between the Jet Propulsion Laboratory (JPL) and Maxar Technologies. It carries a suite of science instruments to accomplish its mission, including imagers, gamma ray and neutron spectrometers, and magnetometers. It also hosts a technology demonstration, the Deep Space Optical Communications (DSOC), and is the first mission to use Hall electric propulsion thrusters beyond lunar orbit. Psyche launched in October of 2023 and is currently undergoing initial checkout before beginning its cruise thrusting.This paper focuses on the off-nominal testing that was conducted on the Guidance, Navigation, and Control (GNC) software after its 2022 launch slip. To verify the system is robust enough to handle off-nominal scenarios, a wide array of GNC related single faults was injected into the system while running a realtime flight simulation on the testbed. The faults were injected during launch, safe mode, and nominal operations spanning a wide variety of mission phases, hardware configurations, and launch conditions, and were chosen to test the vulnerabilities of the system. The faults themselves touched all GNC devices, ranging from solar array deployment failures to biases in the inertial measurement units to leaky thrusters.This paper will also discuss the venues on which testing was conducted. While the GNC algorithms were developed in an environment isolated from the rest of the flight system, the offnominal testing was conducted on the flight software testbeds at JPL, which leverage engineering models of the Psyche Compute Element (PCE) that run Psyche's flight software in its entirety. The PCE interfaces with simulated software models of the GNC devices, plus an environmental model, ephemeris, and dynamics model.Finally, this paper will examine how the results of the offnominal testing resulted in updates to the GNC algorithms, fault protection (FP) parameters, and operational constraints.